Differentiation of c‐Kit+CD24+ natural killer cells into myeloid cells in a GATA‐2‐dependent manner. Issue 3 (27th January 2020) - Song, Boyeong; Lee, Jeong‐Mi; Park, Young‐Jun; Kim, Il‐Kyu; Kim, Byung‐Seok; Shin, Kwang‐Soo; Jeon, Insu; Koh, Choong‐Hyun; Bae, Eun‐Ah; Seo, Hyungseok; Byun, Youngro; Kang, Chang‐Yuil
Abstract: Myeloid progenitor cells have generally been considered the predominant source of myeloid cells under steady‐state conditions. Here we show that NK cells contributed to a myeloid cell lineage pool in naïve and tumor‐bearing mice. Using fate tracing of NKp46 + cells, we found that myeloid cells could be derived from NK cells. Notably, among mature CD11b + CD27 + NK cells, c‐Kit + CD24 + NK cells were capable of differentiating into a range of myeloid lineages in vitro and produced neutrophils and monocytes in vivo. The differentiation was completely inhibited by NK‐stimulating cytokines. In addition to the potential for differentiation into myeloid cells, c‐Kit + CD24 + NK cells retained NK cell phenotypes and effector functions. Mechanistically, GATA‐2 was necessary for the differentiation of c‐Kit + CD24 + NK cells. Therefore, we discovered that GATA‐2‐dependent differentiation of c‐Kit + CD24 + NK cells contributes to myeloid cell development and identified a novel pathway for myeloid lineage commitment under physiological conditions.